(untitled) (CIPEEX, 2025)
The present study aims to show that even with the advances made in labor legislation for the benefit of women, they continue to suffer discrimination in the labor market. An analysis of Law 14,611/23 was carried out, which addresses the obligation of equal pay within companies and its challenges, bearing in mind that women have been fighting for equality in all aspects, be it salary, property, and even achieving leadership positions. The research methodology adopted was a bibliographic review to understand the perception of researchers on the chosen topic, with the aim of clarifying the points presented in the text. Therefore, the objective was to report the influence of patriarchy on society and its negative repercussions, from the perspective of the sexual division of labor, which still affects women considerably. It was concluded, based on the analysis of official data, that wage inequality in the labor market exists and, even though women have higher levels of education, they still earn less than men and occupy less prominent positions.